2018
DOI: 10.1155/2018/3620293
|View full text |Cite
|
Sign up to set email alerts
|

Early Gastric Cancer with Purely Enteroblastic Differentiation and No Conventional Adenocarcinoma Component

Abstract: Gastric carcinoma with enteroblastic differentiation (GCED) is a rare variant of gastric carcinoma, and a part of GCED produces alpha-fetoprotein. GCED is characterized by cells with clear cytoplasm and a tubulopapillary and solid growth pattern resembling those in the primitive gut. GCED is typically overlaid by a conventional adenocarcinoma (CA) component, implying that CA in the mucosa differentiates into GCED during tumor invasion and proliferation. We present the case of a 73-year-old woman with a 10-mm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Histologically, the tumour cells are columnar or cuboidal with clear cytoplasm containing abundant glycogen and a tubulopapillary architecture. 6,7 The abundance of glycogen and clear cell morphology may impart a somewhat tigroid (granular, reticulated) background on Romanowsky-based stains, as was evident in our case. On IHC, the tumour cells are known to express several oncofetal proteins, including AFP, SALL4, and glypican-3.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Histologically, the tumour cells are columnar or cuboidal with clear cytoplasm containing abundant glycogen and a tubulopapillary architecture. 6,7 The abundance of glycogen and clear cell morphology may impart a somewhat tigroid (granular, reticulated) background on Romanowsky-based stains, as was evident in our case. On IHC, the tumour cells are known to express several oncofetal proteins, including AFP, SALL4, and glypican-3.…”
Section: Discussionsupporting
confidence: 54%
“…Anisocytosis, nuclear contour irregularity, and prominent nucleoli are key features. Histologically, the tumour cells are columnar or cuboidal with clear cytoplasm containing abundant glycogen and a tubulopapillary architecture 6,7 . The abundance of glycogen and clear cell morphology may impart a somewhat tigroid (granular, reticulated) background on Romanowsky‐based stains, as was evident in our case.…”
Section: Discussionsupporting
confidence: 52%
“…They are classified by images of hematoxylin and eosin staining and immunostaining, and SALL4 and Glypican3 are known as sensitive markers for the diagnosis of not only AFPGC but also GAED. 4,5 In our case, the microscopic pathological image with hematoxylin and eosin staining revealed tumor cells with pale cytoplasm, and in addition to AFP, the immunostaining of SALL4 and Glypican3 was positive. For endoscopists, pathological specimen confirmation and discussion with a pathologist are important for diagnosing AFP-producing early-stage gastric cancer.…”
Section: Discussionmentioning
confidence: 51%
“…AFP-producing early-stage gastric cancer was reported in 47 patients from 1990 to 2022, including our cases (Table 1). [3][4][5][6][7][8][9][10] Additionally, we could not find reports regarding early-stage cases of AFP-producing gastric cancer outside of Japan. The gross type was IIa+IIc/IIc+IIa in 23 cases (49%), and the histological types were por, tub2, and tub1, in that order.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 7 reported 65 cases and defined CCC as a carcinoma composed of more than 5% of clear cells. To the best of our knowledge, only Terada 9 and Yamada et al 10 have reported the pure form.…”
Section: Discussionmentioning
confidence: 97%